A case of desmoplastic ameloblastoma occupying maxillary sinus - Hideharu Kato; Jouji Nomura; Yoshihiro Matsumura; Toshiro Tagawa (Wolters Kluwer Medknow Publications, 2011)
We report a rare case of desmoplastic ameloblastoma lesion that filled the entire maxillary sinus. The patient visited our hospital with a chief complaint of swelling around the upper left premolars. A panoramic X-ray captured an image of a mixture of ill-defined radiolucency and radiopacity from the swollen area to the maxillary sinus. Computed tomography (CT) and Magnetic resononce imaging (MRI) showed that the lesion occupied almost the entire left maxillary sinus and had entered the nasal cavity. A pathologic diagnosis of ameloblastoma was made after biopsy, and the tumor was removed and the marginal bone curetted under general anesthesia. A CT scan at 4 months postoperatively indicated the presence of residual and recurrent tumor in the area of the upper left lateral incisor, and removal and curettage were performed again. Recurrence may be detected relatively easily based on radiographic characteristics, and therefore follow-up with an X-ray examination such as a CT scan is important.